Analysis of Barriers to the Implementation of Participatory Principles in Implementing the Functions of the Village Consultative Body to Improve - Mukhammad Soleh (LEGAL BRIEF, 2024)
The implementation of Village Government, between the Village Government and the Village Consultative Body must be carried out based on the principles of good governance. The Village Consultative Body has the function of discussing and agreeing on Draft Village Regulations with the Village Head; accommodate and channel the aspirations of the Village community; and supervising the performance of the Village Head. This research aims to analyze the factors that hinder the implementation of participatory principles in carrying out the functions of the Village Consultative Body; in Sukopuro village, Jabung District, Malang Regency. This research uses empirical juridical research methods, a sociological approach, extracting primary data through interviews and observations, while secondary data through literature study and analysis using sociological juridical analysis with the stages of data display, data reduction and drawing conclusions. The results of the research are that the factors inhibiting the implementation of participatory principles in carrying out the functions of the Village Consultative Body are internal factors: the Village Consultative Body (BPD) has not been able to accommodate the wishes of the community optimally; The quality of BPD's Human Resources (HR) is still lacking; Lack of socialization of BPD work programs. External factors: different human resources in the community; Society is less responsive to technological developments; The community is indifferent or does not care about the policies of the Village Government and the Village Consultative Body